Field Data Analysis of Home-Based Stormwater On-Site Detention System - Ngu, J.O.K.; Mah, Darrien Yau Seng; Taib, S.N.L.; Mannan, M.A. (Penerbit UMT, 2022)
This paper describes the field test of a stormwater detention system which is a system designed to hold a specific volume of water and release it slowly over time, in this test case precast concrete modular units are assembled in a residential car porch and connected to a partial roof catchment via a downpipe. Stormwater is held and stored temporarily within the chambers created by the precast concrete pieces. Rainfall and flow data associated with the detention system in terms of the inflow, outflow and water levels data are collected and verification process are performed by comparing the collected data to design data for the intended system. Analyses of five storm events confirm that the estimated design inflow, outflow and water levels in response to 5- and 10-minute 10-year Average Recurrent Intervals (ARI) design rainfall are safe against the actual rainfall and actual detention and discharge performances.